2017
DOI: 10.3390/ijms18081639
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery by Molecular Imaging and Monitoring Therapy Response in Lymphoma

Abstract: Molecular imaging allows a noninvasive assessment of biochemical and biological processes in living subjects. Treatment strategies for malignant lymphoma depend on histology and tumor stage. For the last two decades, molecular imaging has been the mainstay diagnostic test for the staging of malignant lymphoma and the assessment of response to treatment. This technology enhances our understanding of disease and drug activity during preclinical and clinical drug development. Here, we review molecular imaging app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 120 publications
0
12
0
Order By: Relevance
“…Specially, functional assessment at molecular level remains challenging due to a lack of practical strategies and tools that can characterize mAb-based candidates during preclinical and clinical studies. Molecular imaging holds a great potential as a noninvasive visualization of biological processes at the molecular level within intact living organisms [ 113 , 114 ]. Among which, PET is promising for measuring target engagement of mAbs to predict toxicity and efficacy, which has also shown capability for clinical translation [ 115 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Specially, functional assessment at molecular level remains challenging due to a lack of practical strategies and tools that can characterize mAb-based candidates during preclinical and clinical studies. Molecular imaging holds a great potential as a noninvasive visualization of biological processes at the molecular level within intact living organisms [ 113 , 114 ]. Among which, PET is promising for measuring target engagement of mAbs to predict toxicity and efficacy, which has also shown capability for clinical translation [ 115 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…MRI and combined PET/CT are the main molecular imaging techniques currently used to shape diagnosis, therapy assessment, and treatment to aid precision medicine in the central nervous system. There is growing evidence of the utility of molecular imaging in the clinic for the prognosis and diagnosis of tumors, immune‐, cardiovascular‐, and CNS‐ diseases (Forsythe & Newby, 2018; Kalimuthu, Jeong, Oh, & Ahn, 2017; Lipsman et al, 2018; Penet, Krishnamachary, Chen, Jin, & Bhujwalla, 2014; Signore et al, 2018; Zukotynski & Kim, 2017). In a clinical study, Tang et al (2009) found that ultrasmall superparamagnetic iron oxide nanoparticles (USPION)‐enhanced MRI was able to define the therapeutic effect of atorvastatin on carotid plaque inflammation, as USPION was phagocytosed by macrophages in atherosclerotic plaques.…”
Section: Imaging As a Central Component Of Precision Medicinementioning
confidence: 99%
“…The obstacles of FLI include the risk of the altered homing character of EVs and limited depth penetration for in vivo imaging (Gangadaran et al, 2017). However, BLI and FLI have the advantages of high sensitivity, low cost, and high‐throughput capability, which are important for preclinical studies (Kalimuthu et al, 2017). By contrast, direct labeling with radionuclides for PET magnetic particles for MRI and gold nanoparticles (GNPs) for CT can be easily translated as they are widely used in preclinical and clinical studies.…”
Section: Labeling Of Evs For Clinical Applicationsmentioning
confidence: 99%
“…Taken together, 64 Cu-ATSM not only is PET imaging agent, but it also is a potential agent for internal radiotherapy (28). (21,29,30). MRI can provide morphological and pathophysiological information in living subjects (29).…”
Section: Positron Emission Tomographymentioning
confidence: 99%